2020
DOI: 10.1016/j.heliyon.2020.e04126
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, biological evaluation and model membrane studies on metal complexes containing aromatic N,O-chelate ligands

Abstract: Novel lanthanide (Ln) compounds [Ln(L) 2 ]Cl . xH 2 O (Ln ¼ La 3þ , Ce 3þ , Sm 3þ ) containing aromatic N,O-chelate ligands [HL1 ¼ 4-amino-2-(1H-benzimidazol-2-yl)phenol; HL2 ¼ 5-amino-2-(1H-benzimidazol-2-yl)phenol] have been synthesized and structurally characterized by elemental analysis, NMR and IR spectroscopy, molar conductance measurements, and mass spectrometry (MS). The spectroscopic data suggested that the benzimidazolyl-phenol ligands act as N,O-chelate ligands through the iminic nitrogen and phenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 66 publications
(73 reference statements)
0
8
0
Order By: Relevance
“…When comparing the results of the L1 and L2 series, a greater inhibitory effect was observed for the Schiff bases prepared from 2,4-dihydroxybenzaldehyde, which indicates that having an -OH functional group at the para- position of the salicyldene ring is very relevant for the biological behavior of this compound. The outcome of the substitution in the aminophenyl ring was also observed when comparing the results of the L2 series with those of the L4 series, revealing increased inhibitory activity for the 1,3-position compared with the 1,4-position, similar to the effect observed for the position of the amino group in N,O-chelate ligands derived from benzimidazolyl-phenol [ 40 ].…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…When comparing the results of the L1 and L2 series, a greater inhibitory effect was observed for the Schiff bases prepared from 2,4-dihydroxybenzaldehyde, which indicates that having an -OH functional group at the para- position of the salicyldene ring is very relevant for the biological behavior of this compound. The outcome of the substitution in the aminophenyl ring was also observed when comparing the results of the L2 series with those of the L4 series, revealing increased inhibitory activity for the 1,3-position compared with the 1,4-position, similar to the effect observed for the position of the amino group in N,O-chelate ligands derived from benzimidazolyl-phenol [ 40 ].…”
Section: Resultsmentioning
confidence: 89%
“…Additionally, the molecular docking studies discussed below indicated that the ligands could interact with molecular targets through hydrophilic bonds and conventional hydrogen bonds, in addition to pi-alkyl interactions with the three aromatic rings, which may also be the mechanisms involved in the inhibition of human DNA topoisomerase I [ 41 ]. Another selective target might be phosphatidylserine (anionic phospholipid), which is found on the outer membrane of cancerous cells and may electrostatically attract the positively charged ligand when in keto-enolic equilibria [ 40 ], as occurs for salen-type Schiff bases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The distance between two nodes was set to d (nm), and the surface area was set to (50 d ) 2 (nm 2 ). The sizes of each ligand and the precursors were modeled using the MOLview tool, assuming a spherical model. The Carish and TMA precursors dissociated into *2O–Ru–2­[C 7 H 11 O 2 ] and *2O–Al­(CH 3 ) after surface adsorption through the loss of 2 CO ligands and 2 CH 3 groups, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Studies including compounds with the benzimidazole motif on their structures are interesting for the scientific community, not only because of their known antibacterial and cytotoxic properties [ 18 , 19 , 20 ], but because of the high conjugation that they exhibit when forming Schiff bases, improving their electronic characteristics and often conferring fluorescent properties that facilitate the monitoring of morphology in microorganisms subjected to these types of drugs [ 21 ].…”
Section: Introductionmentioning
confidence: 99%